HIV-related knowledge among people living with HIV/AIDS in Kelantan, Malaysia. Issue 2 (2nd April 2016) - Saddki, Norkhafizah; Sulaiman, Zaharah; Abdullah, Sarimah; Zakaria, Norzila; Mohamad, Norsarwany; Ab Razak, Asrenee; Zainan Abidin, Zarina
ABSTRACT: The authors of this cross-sectional study aims to translate and validate the brief HIV Knowledge Questionnaire (HIV-KQ-18) into Malay language, to assess HIV-related knowledge and its sociodemographic predictors among a sample of people living with HIV/AIDS in Kelantan, Malaysia. A total of 160 HIV patients participated in this study. The Malay version of HIV-KQ-18 showed good internal consistency with Cronbach's α value of .78. Intraclass correlation coefficient was 0.76 (95% confidence interval, 0.61 to 0.85). The HIV-KQ-18 score was normally distributed with a mean of 9.7 ( SD  = 3.78). The mean percentage of correct responses was 53.7 ( SD  = 21.0). Higher education level and longer period of living with HIV were significantly associated with better HIV knowledge. In conclusion, the Malay version of HIV-KQ-18 is a valid and reliable instrument to assess HIV-related knowledge, which was found to be lacking in certain aspects among our sample.